Energy saving performance assessment and lessons learned from the operation of an active phase change materials system in a multi-storey building in Melbourne. (15th March 2019) - Alam, Morshed; Zou, Patrick X.W.; Sanjayan, Jay; Ramakrishnan, Sayanthan
Highlights: Performance of an active PCM system installed in an 11 storey building was studied. Operational parameters of the active PCM system were monitored for 25 months. PCM reduced chiller cooling load by 12–37% in winter but remained inactive in summer. PCM only utilized 15% of its heat storage capacity to shift the peak cooling load. The factors that contributed to the underperformance of active PCM were reported. Abstract: While the energy saving performance of an active phase change materials (PCMs) system in buildings has been widely investigated using prototype-scale experiments and numerical assessments, their performance during the operational phase of a real building has been less understood. This study assessed the energy-saving performance of an active PCM system installed in an eleven storey building in Melbourne. Macro-encapsulated PCM with the phase transition temperature of 15 °C was installed in a large PCM tank. Water was used as the heat transfer fluid (HTF) to extract and store cooling energy from the PCM tank. The performance of the active PCM system was monitored for 25 consecutive months, and the results were analyzed on a seasonal basis. Building design documents and the maintenance manuals were studied to understand the difference between design intent and actual operation. The analyzed results revealed that the active PCM system reduced cooling load on the chiller by 12–37% only during colder months, but, remained dormant during the summer. Even in the case of maximum effectiveness, the PCM tank only utilized 15% of its available heat storage capacity to reduce the cooling load. The factors that contributed to the underperformance of active PCM system include mismatch between designed and actual operation of the PCM system, inefficient operation logic of the system, poor material quality, and limited knowledge of maintenance staffs during the operation stage. The lessons learned from the operation of this active PCM system in this multi-storey building were reported and discussed.